State and trait anxiety levels of adolescent wrestlers - Orhan, I.; Ugurlu, A. (International Journal of Applied Exercise Physiology, 2020)
Wrestling is a complex sports requiring several high level motoric performance demands such as strength, endurance, flexibility, speed, balance. As mentioned performance demands, psychological state is a strong determinant of success in wrestling as in many other sports. Thus, this study aimed to investigate the state and trait anxiety levels of adolescent wrestlers according to several variables like region, housing, doing traditional oil wrestling and achievement to reach the podium. A total of 101 competitive adolescent wrestlers aged 12 to 18 participated in this study. State and trait anxiety levels of participants were determined using The State-Trait Anxiety Inventory (STAI), and personal information form prepared by researchers was used to collect demographic information. As a result, statistical significance was noted in state anxiety levels of adolescent wrestlers according to region. Wrestlers from Elmali were determined to have higher level of state anxiety compared to wrestlers from Antalya city center and Korkuteli regions. No further statistical significance was determined. In conclusion, region can be stated as a moderator of staten anxiety level and the need for further research should be considered from different perspectives to get underpinning mechanisms of psychological performance parameters.